Direct current bias effects on grain boundary Schottky barriers in CaCu3Ti4O12 - Kim, ID; Rothschild, A; Tuller, HL (AMER INST PHYSICS, 2006)
CaCu3Ti4O12 exhibits an unusually high dielectric constant on the order of 10(5) and highly nonlinear I-V characteristics. Impedance spectroscopy measurements carried out in this work point to the crucial role played by grain boundary barriers in controlling the electrical properties of this material. Under dc bias, the grain boundary resistance decreases, followed by a precipitous breakdown at higher applied voltages. The barrier height is estimated to be similar to 0.82 eV. The grain conductivity shows a transition from a negative temperature coefficient of resistance with activation energy of similar to 0.08 eV to a positive temperature coefficient of resistance at 280 degrees C suggesting a transition from impurity ionization to scattering controlled mobility in the carrier saturation region.
Keywords: HIGH-DIELECTRIC-CONSTANT; COPPER-TITANATE